Investigating the effects of comprehensive smoke-free legislation on neonatal and infant mortality in Thailand using the synthetic control method - Márta K. Radó; Frank J. van Lenthe; Aziz Sheikh; Jasper V. Been (EClinicalMedicine, 2020)
Background: Almost all of the evidence on the benefits of smoke-free legislation on child health comes from evaluations in high-income countries. We investigated the effects of Thailand's 2010 comprehensive smoke-free legislation on neonatal and infant mortality. Methods: To overcome some of the methodological issues inherent to traditional quasi-experimental methods, we applied the novel synthetic control approach. Using 2001–2017 country-level panel data from the World Bank and Penn World datasets, we estimated the effects of smoke-free legislation as the difference between the outcome trends in Thailand versus those in a synthetic control country. The synthetic control country was composed of ‘control’ middle-income countries without comprehensive smoke-free legislation to recreate trends in Thailand in the 2001–2009 pre-legislation outcomes and covariates. We compared the legislation effects to ‘placebo effects’ obtained for each control country by fictitiously assuming that comprehensive smoke-free legislation was introduced there in 2010, similar to Thailand. Findings: Neonatal and infant mortality decreased by 2.9% and 2.8%/year respectively following smoke-free legislation, with an estimated 7463 infant deaths (including 4623 neonatal deaths) having been averted over eight years. The results were robust to different specifications of the control countries. Comparison with placebo effects indicated that the findings were unlikely to be attributable to factors other than the smoke-free legislation. Interpretation: Expanding comprehensive smoke-free policies to middle-income countries can support national efforts to achieve Sustainable Development Goal 3.2 for reducing preventable early-life deaths. Funding: Netherlands Lung Foundation, HDRUK, Asthma UK center for Applied Research and NIHR Global Respiratory Health Unit (RESPIRE).